Effects of 12 Weeks Resistance Training on Serum Irisin in Older Male Adults - Zhao, Jiexiu; Su, Zhongjun; Qu, Chaoyi; Dong, Yanan (Frontiers in Physiology, 2017)
Background: To assess the effects of resistance training on circulating irisin concentration in older adults, and to determine the association between resistance training induced alteration of irisin and body fat. Methods: Seventeen older adults (mean age is 62.1 years old) were randomized into old control group (male, n=7), and old training group (male, n=10). The control group has no any exercise intervention. The resistance training group underwent leg muscle strength and core strength training program 2 times/wk, 55 min/class for 12 weeks. Before and after the intervention, we evaluated serum irisin level and body composition. Results: Serum irisin level was significantly increased in the resistance training group after the intervention period (P < 0.01), but not in the control group. In the resistance training group, the reduction in whole-body fat percent was negatively correlated with the change in serum irisin level (r = −0.705, P < 0.05). Conclusion: After the 12 weeks intervention, circulating irisin levels were significantly elevated in the older adults. These results suggest a possible role for secreted irisin in the resistance exercise-induced alteration of body fat in older adults.